Wind, waves, tides, and human error? – Influences on litter abundance and composition on German North Sea coastlines: An exploratory analysis. (September 2019) - Schöneich-Argent, Rosanna Isabel; Hillmann, Frank; Cordes, Daniel; Wansing, Raphael Andreas Daniel; Merder, Julian; Freund, Jan Alfred; Freund, Holger
Abstract: Being globally and locally prevalent, beach litter has been monitored at 29 sites along the German North Sea coastline. This study offers an exploratory analysis of data from 1991 to 2016. Schleswig-Holstein exhibited lower mean litter pollution levels than Lower Saxony, possibly because the locations in Lower Saxony are situated along the main coastal current, whereas the North Frisian Islands act as a barrier for the mainland sites in Schleswig-Holstein. Locations close to the Elbe estuary had significantly larger amounts of debris, likely receiving litter from marine and riverine sources. No clear overall pattern in litter abundance or composition could be detected. Significant quantitative similarities between debris types were inconsistent. The effect of wind, tides, and exposure appeared to be marginal. Recurring data inconsistencies, gaps, and outliers were partly attributed to human error. This could be reduced through hypothesis-driven monitoring with a simpler litter classification and continuous data checking. Highlights: 25 years of beach litter data from the German North Sea coast were analyzed. The data revealed spatio-temporal heterogeneity in litter quantity and composition. The influence of environmental factors considered for this study appeared marginal. Data gaps and recurring inconsistencies hampered data processing. A consistent, targeted, and motivated data collection should be aimed for.